Exploring Ethical Leadership in Woman Organization - Laili, Januariya; 'Aini, Siti Nur (Ikatan Cendikiawan Ilmu Pendidikan Islam (ICIPI), 2026)
The young women’s organization “X” focuses on issues of gender equality, religion, society, and culture. Leadership plays a crucial role in ensuring the organization’s sustainability amid various internal and external challenges. This study aims to explore the practice of ethical leadership within Organization X in Jember Regency. A mixed-methods approach with a sequential explanatory design was employed. Quantitative data were collected through questionnaires containing open-ended questions to obtain an initial overview of the phenomenon, followed by qualitative data collection through in-depth interviews to deepen and clarify the findings. The participants in this study were branch-level leaders of Organization X. The findings indicate that leaders in Organization X are expected to consistently serve as moral role models, demonstrating alignment between their words and actions as representatives of the organization’s core values. In the dimension of care for others, leadership is perceived as a participatory process that actively involves members in decision-making and the implementation of organizational programs, reflecting principles of deliberation and empowerment. Meanwhile, in the dimension of accountability and compliance, leaders are required to adhere not only to organizational regulations but also to prevailing social norms within the broader community. These findings suggest that despite its strong and firm ideological foundation, Organization X demonstrates contextual flexibility in social engagement as part of its da‘wah strategy.